ANALISIS KONDISI KEUANGAN PT. HUTAMA KARYA PADA SAAT PENYELESAIAN KASUS PROYEK IPDN - Budi Dharma; Wahyu Andriansyah Naibaho; Indah Aryani (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out how the financial condition happened in the case of the IPDN project at the company Pt. Hutama Karya. In this case, the project case is reviewed by analyzing the financial problems that occur in it. The research method used is quantitative by taking a comparative calculation approach between 2021 and 2022, which type of research uses a secondary data approach obtained from annual financial reports for a period of 1 year, namely 2021-2022, books, journals, and other sources. other. The results of the research can be concluded that the company PT. Hutama Karya experienced a decrease in profitability in 2022 where the performance of financial companies in the 2022 period decreased, from the results of the gross profit margin analysis it can be seen that the proportion of company revenue decreased by a difference of 1% and from the results of the profitability analysis using the ratio of return on assets decreased reached 0.08% above the profit from managing the company's resources and assets.